Evidence of multidimensionality in the ALSFRS-R Scale: a critical appraisal on its measurement properties using Rasch analysis. Issue 12 (20th March 2013) - Franchignoni, Franco; Mora, Gabriele; Giordano, Andrea; Volanti, Paolo; Chiò, Adriano
Abstract : Objective: To examine dimensionality, reliability and validity of the Amyotrophic Lateral Sclerosis Functional Rating Scale-revised (ALSFRS-R) using traditional classical test theory methods and Rasch analysis in order to provide a rationale for possible improvement of its metric quality. Methods: Methodological research on ALSFRS-R collected in a consecutive sample of 485 patients with amyotrophic lateral sclerosis (ALS) attending three tertiary ALS centres. Results: The ALSFRS-R items showed good internal consistency but dimensionality analysis argues against the use of ALSFRS-R as a single score because the scale lacks unidimensionality. Parallel analysis and exploratory factor analysis revealed three factors representing the following domains: (1) bulbar function; (2) fine and gross motor function; and (3) respiratory function. Rasch analysis showed that all items in each domain fitted the respective constructs to measure, except for item No 9 'climbing stairs' and item No 12 'respiratory insufficiency'. Rating categories did not comply with the criteria for category functioning. Collapsing the scale's 5 level ratings into 3 levels improved its metric quality. Conclusions: The ALSFRS-R fails to satisfy rigorous measurement standards and should be, at least in part, revised. At present, ALSFRS-R should be considered as a profile of mean scores from three different domains (bulbar, motor and respiratory functions) more than a global total score. Further studies on ALSFRS-R using modern psychometric methods are warranted to confirm our findings and refine the metric quality of this scale, through a step by step process.